Why do people lie? / Shahrul Muhazad - Muhazad, Shahrul (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
Lying is a universal human behaviour that has been around since the dawn of civilization. People lie for range of reasons, from harmless white lies to serious and deliberate falsehoods. Although lying can have negative consequences, such as damaging relationships, loss of trust, and even legal penalties, it remains a common behaviour in many societies. So, why do people lie? One of the most common reasons for lying is to avoid consequences. For example, a student might lie about why they missed an exam, a worker might lie about why they were late for meetings, or someone might lie about their age to avoid being rejected. People lie to escape responsibility or punishment, and sometimes they believe that lying is the only way to save face or protect themselves. Another reason why people lie is to gain advantage or to manipulate others. For example, a person might lie about their qualification or achievements to land a job or get a promotion. Salespeople often lie about the features of benefits of a product to make a sale. People also lie to obtain power or control over others, such as lying to gain trust or manipulate a situation to their advantage.